Improving Students’ Writing Ability in Personal Recount Text Using Google Jamboard - Susanti, Arik; Agung, Elsha Lintang (JOLLT Journal of Languages and Language Teaching, 2023)
Writing is a vital ability for students to develop their communication skills. Nevertheless, some students believe that writing skills are challenging. Therefore, Google Jamboard can facilitate the learning of the writing process, as it provides opportunities for collaboratively enhancing learning experiences. The purpose of this study was to examine the efficacy of Google Jamboard in enhancing students’ ability to compose personal recount texts. There was no control or comparison in the pre-experimental design. A private vocational high school in Surabaya served as the location. There were 34 pupils in the tenth grade from a Surabaya private vocational high school involved. The instruments were a pre-test and post-test along with a writing rubric. The data were obtained by administering a writing test before and after the implementation of Google Jamboard. Using SPSS version 22, a paired sample T-test was utilized to analyze the data. The results demonstrate a significant gain in the mean score between the pre-test and post-test, with an increase of 19.97 points. Additionally, the two-tailed significance value (Sig) is below 0.05, specifically 0.000. This statement implies that the alternative hypothesis (Ha) has been approved. To sum up, Google Jamboard can enhance students’ personal recount writing skills. It is recommended that other researchers utilize Google Jamboard to teach additional English skills.